Dental Medicine Students Perception on the Effectiveness of Problem Based Learning (PBL) Class Using Online Learning Method (Medico Legal Update, 2021)
Background: The main concern of universities is regarding the quality and effectiveness of education. Atotal of 32 dentistry faculties in Indonesia have implemented Problem Based Learning (PBL) classes in theirlearning curriculum. Some dentistry faculties have actively used student-centered learning method, andare no longer teacher-centered. According to the results of the 2017 Indonesian Internet Service ProvidersAssociation, the prevalence for Indonesian (Undergraduate/Diploma) students as Internet users reached79.23%.Purpose: To describe the perception of Universitas Airlangga Faculty of Dental Medicine students on theeffectiveness of the Problem Based Learning (PBL) class using the Online Learning method.Method: Data was collected from the distribution of questionnaires to students of Universitas Airlangga,Faculty of Dental Medicine semesters 1, 3, 5, and 7. Then a descriptive statistical test was conducted.Results: The percentage of respondents who considered effective Problem Based Learning (PBL) classesusing online learning method was 52.4%, very effective at 5.8%, very ineffective at 2.9%, no opinion at14.6%, and ineffective at 24.3%.Conclusion: The majority of Universitas Airlangga Faculty of Dental Medicine students have an effectiveperception of the Problem Based Learning (PBL) class using the Online Learning method.